Of literature and lattes : [large type] a novel - Reay, Katherine, 1970- (Center Point Large Print, 2020)
"After fleeing her hometown three years earlier, Alyssa Harrison never planned to return. Then the Silicon Valley start-up she worked for collapsed and turned her world upside down. She is broke, under FBI investigation, and without a place to go. Having exhausted every option, she comes home to Winsome, Illinois, to regroup then move on as quickly as possible. Yet, as friends and family welcome her back, Alyssa begins to see a place for herself in this small Midwestern community.Jeremy Mitchell moved from Seattle to Winsome to be near his daughter and to open the coffee shop he's been dreaming of for years. Problem is, the business is bleeding money - and he's not quite sure why. When he meets Alyssa, he senses an immediate connection, but what he needs most is someone to help him save his floundering business. After asking for her help, he wonders if something might grow between them - but forces beyond their control soon complicate their already complex lives, and the future they both hoped for is not at all what they anticipated.With the help of Winsome's small-town charm and quirky residents, Alyssa and Jeremy discover the beauty and romance of second chances"--Provided by publisher.